How Do Children With Mild Intellectual Disabilities Perceive Loneliness? - Kalliopi Papoutsaki; Angeliki Gena; Efrosini Kalyva (Europe's Journal of Psychology, 2013)
The present study examined 154 children with mild intellectual disability (MID) attending special schools with regard to their reports of loneliness. Semi-structured interviews revealed that more than half of the students with MID reported feelings of loneliness. They tend to have as friends children from their neighborhood, friends of their siblings, children of their parents’ friends and from their school. Lonely children with MID tend to attribute their isolation to interpersonal deficits, lack of contact with peers and physical appearance, while one fourth cannot justify why they do not have any friends. Children with MID report that they withdraw from social interactions, engage in solitary activities and actively look for friends to cope with their feelings of loneliness and rejection, while very few resort to physical or verbal aggression. Moreover, boys and children living in smaller towns reported less feelings of loneliness than girls and children living in the capital.